2022
DOI: 10.29374/2527-2179.bjvm00132
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic evaluation of working dogs of the Military Police of Rio de Janeiro: effects of the breed and body weight

Abstract: The Military Police of Rio de Janeiro state use dogs as a decisive tool for patrol and detection of drugs, weapons, and explosives. Complementary tests, such as echocardiography, are essential to maintain the integrity of these animals. This study aimed to evaluate the echocardiographic parameters of the working dogs belonging to the Military Police of Rio de Janeiro and compare them with the available data. Echocardiographic evaluation was performed on 48 healthy adult dogs from the Canine Action Battalion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Each study was based on a different number of individuals. Some breeds exhibited similar values to previous studies, while others showed slight variations, possibly due to factors like somatotype and physical activity levels [2,31,44,48].…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…Each study was based on a different number of individuals. Some breeds exhibited similar values to previous studies, while others showed slight variations, possibly due to factors like somatotype and physical activity levels [2,31,44,48].…”
Section: Resultssupporting
confidence: 79%
“…One German Shepherd study showed a significant relationship between gender and left ventricular posterior wall thickness in systole and diastole [25]. The other two studies [2,26] could not confirm this difference as the authors did not present different information for males and females. Male Kangal dogs had higher left ventricular posterior wall thickness than females [50].…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Dogs have been used more frequently by men as a work tool (Gordon, 2018;Lima et al, 2022), and one of the activities in which they are widely used is the search, rescue, and recovery service of the military organs (Corpo de Bombeiros Militar de Goiás, 2020; Moraes et al, 2017). This activity triggers significant metabolic changes (Diverio et al, 2016;Rovira et al, 2008) that begin as a consequence of the physical training routine that occurs from the first year of life of the animal and lasts throughout its useful life in the military service (Corpo de Bombeiros Militar de Goiás, 2020).…”
Section: Introductionmentioning
confidence: 99%